Impact of assimilating wind retrievals from high‐frequency radar on COAMPS forecasts in the Chesapeake Bay - Brian K. Blaylock; Daniel P. Tyndall; Philip A. Muscarella; Kelsey Brunner (Atmospheric Science Letters, 2023)
Abstract Wind retrievals from high‐frequency radars (HFRs) provide high‐density, hourly wind estimates over the ocean near the coast. These wind retrievals are a promising new source of near‐surface wind estimates in coastal regions where it is difficult to deploy large networks of buoys and where scatterometers cannot observe because of land contamination. In addition to improving ocean monitoring, these wind retrievals are also useful in numerical weather prediction. The wind estimates are retrieved from the HFR Doppler spectra in conjunction with the Simulating WAves Nearshore (SWAN) model, HFR forward model, and HFR adjoint model. In this work, wind retrievals were generated from three Coastal Ocean Dynamics Applications Radar (CODAR) SeaSonde HFR sites located near the mouth of the Chesapeake Bay in August 2017 and assimilated in the Coupled Ocean/Atmosphere Mesoscale Prediction System® (COAMPS) model. The impact of the assimilated HFR wind retrievals on near‐surface weather forecasts is measured with adjoint‐derived forecast sensitivity observation impact (FSOI) and a comparison to forecasts from a data‐denial observing system experiment (OSE). The FSOI measurement indicates the HFR winds had neutral impact on the 12‐h forecast while the OSE comparison suggests a small improvement in the 10‐m u and v winds at lead times up to 36 h. Compared to a similar study in the Southern California Bight, the small impact on the forecast seen in this Chesapeake Bay study could be related to there being a smaller number of wind retrievals in a smaller region during a period where the HFR wind retrievals were already similar to the background wind field. We suggest that HFR wind retrievals used for numerical weather prediction may be more beneficial when generated for long swaths of coastlines rather than small, isolated areas.